2008
DOI: 10.1007/s11248-008-9210-7
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic mice expressing the Peripherin-EGFP genomic reporter display intrinsic peripheral nervous system fluorescence

Abstract: The development of homologous recombination methods for the precise modification of bacterial artificial chromosomes has allowed the introduction of disease causing mutations or fluorescent reporter genes into human loci for functional studies. We have introduced the EGFP gene into the human PRPH-1 locus to create the Peripherin-EGFP (hPRPH1-G) genomic reporter construct. The hPRPH1-G reporter was used to create transgenic mice with an intrinsically fluorescent peripheral nervous system (PNS). During developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 43 publications
1
18
0
Order By: Relevance
“…We hypothesized that defective pruning of type II SGN fibers could account for the abnormal retention of presynaptic ribbons in Pit1 dw mutants. We took advantage of the Peripherin-GFP (PGFP) transgenic mouse model that has the protein peripherin, a commonly used marker for type II SGNs, labeled with GFP (McLenachan et al, 2008). The breeding of PGFP mice with Pit1 dw mice allowed a specific detection of type II SGNs in both WT and Pit1 dw cochleas from P6 onward (Figure 2A,B).…”
Section: Resultsmentioning
confidence: 99%
“…We hypothesized that defective pruning of type II SGN fibers could account for the abnormal retention of presynaptic ribbons in Pit1 dw mutants. We took advantage of the Peripherin-GFP (PGFP) transgenic mouse model that has the protein peripherin, a commonly used marker for type II SGNs, labeled with GFP (McLenachan et al, 2008). The breeding of PGFP mice with Pit1 dw mice allowed a specific detection of type II SGNs in both WT and Pit1 dw cochleas from P6 onward (Figure 2A,B).…”
Section: Resultsmentioning
confidence: 99%
“…Prph is an interesting candidate because in mammals and zebrafish, it is only expressed in neurons (Fuchs and Weber, 1994; McLenachan et al, 2008), while Xenopus Prph is expressed in neurons, proliferating cells as well as glia (Gervasi et al, 2000). In mammals, peripherin is abundant in PNS neurons and is also expressed in RGCs (McLenachan et al, 2008; Wang et al, 2007). The peripherin response to retinal injury has not been determined in mammals.…”
Section: Discussionmentioning
confidence: 99%
“…As EGFP is one of the most commonly used reporter proteins in mouse transgenics owing to its enhanced photostability and strong fluorescence intensity [20], [21], [22], it is necessary to study its compatibility with the IRES- and F2A-based vector systems. Through the analysis of six locus-specific EGFP knock-in mouse lines that we have generated – Sox9 IRES-EGFP , Sox9 F2A-EGFP , FLAG 3 -Bapx1 F2A-EGFP , Bapx1 IRES-Cre-IRES-EGFP , Bapx1 F2A-Cre-F2A-EGFP and Bapx1 EGFP (hereafter these mouse lines will be denoted by their abbreviated forms as summarized in Table 1), we have demonstrated that both the IRES and F2A reliably co-expressed the concatenated proteins.…”
Section: Introductionmentioning
confidence: 99%